2023
DOI: 10.1111/1471-0307.12941
|View full text |Cite
|
Sign up to set email alerts
|

The Noble Method in the dairy sector as a sustainable production system to improve the nutritional composition of dairy products: A review

Abstract: Sustainable production systems in line with consumer expectations are attractive for the dairy sector. The objective of this review is to examine the benefits of an Italian method, named the Noble Method ('Metodo Nobileâ'), in order to improve the nutritional properties of milk and environmental sustainability. The prohibition of silage and the use of polyphite pastures are some of the rules established by the Noble Method. The greater amount of unsaturated fatty acids and other beneficial compounds found in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…Furthermore, highly productive dairy cows, resulting from genetic improvements, can no longer rely exclusivelyT on grazing to provide the nutrient supply needed to satisfy milk production [87]. If the pasture is of high quality, the proportion of additional feed decreases, while productivity remains unchanged [88], with the additional benefit of obtaining an improvement in the chemical and nutritional composition of milk [89]. Grazing protects the soil from erosion thanks to the strong root system, so there is a benefit of preserving the eco-systems of permanent meadows and pastures [90].…”
Section: The Use Of Pasturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, highly productive dairy cows, resulting from genetic improvements, can no longer rely exclusivelyT on grazing to provide the nutrient supply needed to satisfy milk production [87]. If the pasture is of high quality, the proportion of additional feed decreases, while productivity remains unchanged [88], with the additional benefit of obtaining an improvement in the chemical and nutritional composition of milk [89]. Grazing protects the soil from erosion thanks to the strong root system, so there is a benefit of preserving the eco-systems of permanent meadows and pastures [90].…”
Section: The Use Of Pasturementioning
confidence: 99%
“…Balivo et al [89] reported the health implications of Noble Milk ® consumption for humans. In particular, in this review the importance of the conjugated linoleic acids (CLAs) that are principally present in milk and meat of ruminant is analyzed.…”
Section: Human Healthmentioning
confidence: 99%
“…Animal products give energy and are important sources of high-quality proteins, amino acids, minerals, vitamins, and bioactive compounds necessary for human nutrition. Milk, in particular, is called a complete food, with dairy products as a valuable component of a well-balanced diet (Balivo et al, 2023).…”
mentioning
confidence: 99%
“…A one-factor animal welfare assessment (such as measuring plasma levels of cortisol and serotonin or measuring heart rate variation) does not cover all aspects of animal welfare. Therefore, the use of multi-indicator evaluation protocols is recommended that include a lot of indicators originally developed and conducted for intensive farming systems (Balivo et al, 2023).…”
mentioning
confidence: 99%